Fast-track paediatric and adult congenital cardiac surgery - Alomari, Ammar Mohammad; Zureiqat, Youssef Jamal; Hijazi, Issa; Al-Fawares, Safwan; Al-Dogum, Monir; Mohd, Ashraf Fadel (International Journal of Advances in Medicine, 2024)
Background: Aim of the study was to evaluate the benefits and predictors of success of fast-track and ultra-fast track paediatric and congenital cardiac surgery. Methods: Retrospective observational study of paediatric and adult congenital cardiac surgical patients presented for surgery in period between October 2023 and April 2024 at Queen Alia heart institute (QAHI). Patients’ demographic, clinical and perioperative date were collected and analysed. Patients were divided into groups according to their extubation time: UFTE (Ultra-fast track extubation group, FTE (Fast-track extubation) group, CE (Conventional extubation) group and DE (Delayed extubation) group. All groups were compared in reference to their age, weight, CPB time, AXC time, length of ICU stay and hospitalisation time. Statistical analysis was done to determine the benefits of early extubation after paediatric and congenital cardiac surgery. Predictors of early and DE were studied. Results: Data of 73 paediatric and adult congenital cardiac surgical patients was reviewed and analysed. Patients were 37 males and 36 females. Average age of patients was 11.1 years (ranged from 5 days to 57 years). Average weight of patients was 29.3 kg (ranged from 2.4 to 109 kg) and average height was 104.8 cm. Average time of tracheal extubation was 13.1 hours (ranged from 0 to 168 hours). UFTE was accomplished in 11 patients (15.1%). FTE was done in 19 patients (26%). CE (between was 6 and 24 hours) was carried out in 38 patients (52.1%) and DE (after more than 24 hours) was noted in 5 patients (6.8%). The average ICU stay was 3 days (ranged from 1 to 15 days). Patients from the UFTE group had the shortest average ICU stay of 1.2 days, while patients from the FTE group had an average ICU stay of 1.9 days. Patients from the CE and the DE groups had an average ICU stay of 4 days and 9.4 days, respectively. Length of hospitalisation was shortest in the UFTE group with an average of 6 days. The hospitalisation time doubled in the DE group to 12 days. The shorter the CPB and AXC times the more likely patients were to have UFTE and FTE. Neonates were less likely to have UFTE and FTE. Conclusions: UFTE and FTE were associated with shorter ICU stay and hospitalisation time. Predictors of UFTE and FTE were simple cardiac procedures, shorter CPB and AXC durations. Neonatal age and low body weight paediatric cardiac surgical patients were predictors for conventional or DE.